Diabetes mellitus and the impact on triglycerides - Grigore, Ionica; Gurău, Gabriela; Gurău, Tudor Vladimir; Tutunaru, Dana; Țocu, George; Țovîrnac, Andreea Nicoleta; Neagu, Andrei; Goroftei, Larisa; Ciobotaru, Octavian Cătălin; Ciobotaru, Oana Roxana (Technium BioChemMed, 2022)
Atherosclerosis at the diabetic patient is based on lipoproteins in the form of small and dense particles with an increased capacity for subendothelial penetration and the production of atheroma plaque. We conducted a retrospective study on a number of 217 patients with diabetes mellitus, with an average age of 61.53 years, being analyzed the importance of age, sex, type of diabetes, body mass index on triglyceride values. Although no significant correlations were found between body mass index and triglyceride value, to improve glycemic control and lipid profile in obese patients with diabetes, weight loss is recommended No statistical correlation was found between the value of the body mass index and glycated hemoglobin, respectively the value of triglycerides, there was observed a correlation, even if it was weak, between the value of glycated hemoglobin and triglycerides, underlining the importance of a permanent glycemic control in the prevention of atherosclerosis.